Impact of Monensin Sodium and Essential Limonene Oil on the Fermentation and Chemical Composition of Total Mixed Ration Silages with Moisture Variations - Ronnie Coêlho de Andrade; Marco Antonio Previdelli Orrico Junior; Yara América da Silva; Marciana Retore; Tatiane Fernandes; Ana Carolina Amorim Orrico; Fernando Miranda de Vargas Junior; Isabele Paola de Oliveira Amaral (Agriculture, 2024)
Monensin and essential oils have antimicrobial properties that may impact silage fermentation. The present study was divided into two trials to evaluate the effects of monensin (MON) and essential limonene oils (ELO) as additives in the ensiling of total mixed ration (TMR). In the first assay, TMR was tested with sheep in growth (65% dry matter—DM) using the following treatments: control (no additive), MON35 (35 mg of monensina per kg of DM), MON45 (45 mg of monensina per kg of DM), ELO300 (300 mg of essential limonene oil per kg of DM), and ELO600 (600 mg of essential limonene oil per kg of DM). In the second assay, the same treatments were used in TMR for lactating cows under two moisture conditions (30% and 40% DM). The parameters assessed included fermentative losses, short-chain fatty acid profiles, aerobic stability (hours needed for silage to reach 2 °C above ambient), chemical composition, and in vitro DM digestibility of the silages. Treatment averages were compared using the Scott–Knott test at 5% significance. In the first assay, the treatments with ELO had the lowest (p < 0.05) pH values and the highest (p < 0.05) lactic acid concentrations, with treatment ELO600 leading to the highest (p < 0.05) aerobic stability (297.88 h). Only the starch contents of the ELO treatments were lower (p < 0.05) than the others. In the second assay, the silages with the highest moisture contents and ELO600 exhibited the lowest (p < 0.05) values of DM recovery, lactic acid, and pH. The highest (p < 0.05) lactic acid:acetic acid ratios were observed in the silages with the most moisture added with MON35 and MON45. The use of MON and ELO increased aerobic stability, with the highest (p < 0.05) values observed for ELO600 and MON35. The treatments with MON and ELO resulted in silages with the lowest (p < 0.05) fiber contents and highest ether extract and starch contents when compared with control. Thus, MON and essential oils improve fermentative quality but ELO should be used in lower doses in humid silages to avoid negative fermentation impacts.